The Impact of Authentizotic Climate on the Relationship between Empowerment of Employees and Organizational Citizenship Behaviors: An Applied Study on the Ministry of Higher Education - Mohamed, Howida (The Arab Journal of Administration, 2021)
Institutions are facing today many rapid changes and transformations in pursuit of their objectives. This has led them to reconsider the human capital through adopting new managerial concepts in the field of human resource management. So, it is not surprising that authentizotic climate and its impact on managerial concepts have recently become of much more importance as authentizotic climate is a new trend and a stand-alone strategy. The general strategy of the institution is based on providing healthy workplaces helping individuals to feel satisfied about themselves and their work, adopting an approach enabling workers to share information and decision making with leaders and other workers, establishing trust between management and individuals which is embodied in giving them freedom and independence and motivating them to work collectively within work teams and in transforming from a conventional administrative pattern into an open democratic one which allows human resources to be responsible firstly and lastly for the success or failure of the strategy. The strategy also leads to behaviors beyond what is required and beyond what is expected of the official role through completing works exceeding job description to ensure the success and continuity of the institution. Accordingly, the researcher in this study is seeking to identify the impact of the authentizotic climate on the relationship between worker empowerment and Behaviors of organizational citizenship with a view to helping organizations in general and service ones in particular to apply the authentizotic climate concept using their human resources in addition to spotting the light on the importance of empowering workers and urging service organizations to adopt this approach thus contributing to promoting organizational citizenship Behaviors.